2012
DOI: 10.1007/s10195-012-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of surgical trauma: comparison of conventional and minimally invasive surgical techniques for pertrochanteric fracture surgery based on markers of inflammation (interleukins)

Abstract: Background Fixation of pertrochanteric fracture is undoubtedly an additional trauma after the fracture itself. In elderly patients, it might have an important impact on the whole organism. In the literature we find various techniques to perform this type of surgery. Up to now, there are no parameters validated for quantification of the invasiveness of a surgical procedure; it is therefore still not demonstrated that any method is less invasive than any other. In an effort to find a way to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
1
17
2
Order By: Relevance
“…A similar trend was reported also by Maas et al, who observed a IL-6 peak on day 1 followed by a CRP peak on day 3. 21 In our series, in spite of similar levels in the two groups at admission, albumin levels were higher in HMIE group than in open group at all the time points. 19 Furthermore, increased postoperative CRP levels were associated with the occurrence of postoperative complications and higher 1-year mortality.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A similar trend was reported also by Maas et al, who observed a IL-6 peak on day 1 followed by a CRP peak on day 3. 21 In our series, in spite of similar levels in the two groups at admission, albumin levels were higher in HMIE group than in open group at all the time points. 19 Furthermore, increased postoperative CRP levels were associated with the occurrence of postoperative complications and higher 1-year mortality.…”
Section: Discussioncontrasting
confidence: 47%
“…In fact, IL-6-CRP cascade was also used to quantify and compare the invasiveness of orthopedic procedures techniques with encouraging results. 21 In our series, in spite of similar levels in the two groups at admission, albumin levels were higher in HMIE group than in open group at all the time points. In addition, albumin levels at postoperative day 1 were under the normal values due to extensive fluid replacement during long operative procedures.…”
Section: Discussioncontrasting
confidence: 47%
“…CRP, WBS and IL-6 was greatest in subjects receiving urgent hemiarthroplasty as compared to patients being treated by osteosynthesis. The lesser trauma associated with minimally invasive osteosynthesis techniques was also shown to induce smaller IL-6 elevations (del Prete, Nizegorodcew, & Regazzoni, 2012). In addition several other studies have shown that the minimally invasive surgery is associated with better clinical course.…”
Section: Discussionmentioning
confidence: 96%
“…Increase of interleukin levels, due to the surgery, can greatly increase exposure to the risk of complications and morbidity as they are pro inflammatory cytokines. 5 The conventional DHS fixation requires large incision, more tissue dissection resulting in considerable amount of blood loss and thus requiring blood transfusion and prolonged analgesia for pain control. All these intraoperative and postoperative factors increase the duration of hospital stay and thus the overall cost of surgery.…”
Section: Discussionmentioning
confidence: 99%